2021
DOI: 10.3390/molecules26113089
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Volatile Aldehydes Deriving from In Vitro Lipid Peroxidation in the Breath of Ventilated Patients

Abstract: Exhaled aliphatic aldehydes were proposed as non-invasive biomarkers to detect increased lipid peroxidation in various diseases. As a prelude to clinical application of the multicapillary column–ion mobility spectrometry for the evaluation of aldehyde exhalation, we, therefore: (1) identified the most abundant volatile aliphatic aldehydes originating from in vitro oxidation of various polyunsaturated fatty acids; (2) evaluated emittance of aldehydes from plastic parts of the breathing circuit; (3) conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…For propanal and pentanal a statistically significant increase in maximum has been observed at the highest respiratory rate values. This is in agreement with recent studies carried out on ventilated patients 51 and animal models, 52 showing a positive correlation between breath pentanal and mechanical ventilation pressure, probably because of an increase in lipid peroxidation and oxidation stress. Phenols ( phenol, methyl-phenol and ethyl-phenol) and C2-C6 carboxylic acids have also been linked to oesophago-gastric cancer.…”
Section: Discussionsupporting
confidence: 93%
“…For propanal and pentanal a statistically significant increase in maximum has been observed at the highest respiratory rate values. This is in agreement with recent studies carried out on ventilated patients 51 and animal models, 52 showing a positive correlation between breath pentanal and mechanical ventilation pressure, probably because of an increase in lipid peroxidation and oxidation stress. Phenols ( phenol, methyl-phenol and ethyl-phenol) and C2-C6 carboxylic acids have also been linked to oesophago-gastric cancer.…”
Section: Discussionsupporting
confidence: 93%
“…As mentioned, acetone is a common air compound; however, nonanal and octanal seem to be human-characteristic. Benzaldehyde, heptanal, acetic acid, 2-pentanone, and decanal were identified in at least two independent studies on human emanated analytes, [24,75,105,108,109], proving that they should be targeted with a more profound study and, again, showing the IMS results consistency. Not being able to exhaustively analyze all the addressed works, Table S2 in the Supplementary Materials, summarizes all the identified VOCs by ion mobility spectrometry, enabling a direct comparison among independent works.…”
Section: Vocs Identification Through Imsmentioning
confidence: 85%
“…Similarly, ethanol is also a very common analyte, being identified in [10,[79][80][81]106]. Among all the addressed works underlying this review, hexanal is the most common analyte to be identified [10,24,75,79,105,106,108,109]. On the other hand, some volatile compounds were only identified in a small number of papers.…”
Section: Vocs Identification Through Imsmentioning
confidence: 90%
See 1 more Smart Citation
“…Molecular Mechanism behind Exhaled VOC Profiles of Rats. Through literature research and the KEGG pathway analysis, 23,28,29,43,44 we identified the molecular mechanisms behind 13 biomarkers of exhaled VOCs (Figure 5). We found that the citrate cycle (TCA cycle), the fundamental metabolic pathway for the breakdown of carbohydrates, fats, and proteins in cell mitochondria, 45,46 is closely related to the production of ketones (hydroxyacetone and acetone), acids (acetic acid and lactate), and alcohols (1-propanol and butan-1-ol) in exhaled VOCs.…”
Section: Changes In Nontargeted Serum Metabolites Of Rats After Expos...mentioning
confidence: 99%